Effect of temperature on the performance of perovskite solar cells - Meng, Qi; Chen, Yichuan; Xiao, Yue Yue; Sun, Junjie; Zhang, Xiaobo; Han, Chang Bao; Gao, Hongli; Zhang, Yongzhe; Yan, Hui (Journal of materials science. Materials in electronics, 2021)
The poor stability of perovskite solar cells is a crucial obstacle for its commercial applications. Here, we investigate the thermal stability of the mixed cation organic–inorganic lead halide perovskites (FAPbI 3 ) 1− x MAPb(Br 3− y Cl y ) x films and devices in air atmosphere. The results show that with the increase of heat treatment from 25 to 250 °C, the MA-perovskite decomposed into PbI 2 firstly and the efficiency of corresponding solar cells reduced linearly. For the perovskite film, the increased heat treatment temperature can bring the redshift of the absorption edge leading to the decrease of band gap from 1.569 to 1.508 eV and increase of defect density from 3.87 × 10 17 cm −3 to 9.03 × 10 17 cm −3 . However, a proper heat treatment time (10 min) at certain temperature (85 °C) can passivate defects effectively and improve the efficiency to 16.50%, realizing a 15% relative improvement of average efficiency. This work reveals a detailed thermal decomposition behavior of perovskite material and solar cells, which may provide insights into the stability of perovskite solar cells.